Krisis Finansial Amerika Serikat dan Perekonomian Indonesia - Teguh Sihono (Jurnal Ekonomi dan Pendidikan, 2008)
The United State of year 2007 experience financial crisis that caused by be hidden of mortgage market or credit clogged in property sector reach US$1,8 quintillion. The giant financial institutes in United State, Europe and Japan suffered loss as big as US$160 billion (2007) and US$300 billion (2008) in fact direct number US$1 quintillion of year 2009. This financial crisis in serious condition it by world oil price that highly, rise it commodity price, fall consumption, Fed rate that high, production fall, inflation pressure, unemployment rising, fall of stock price, fall growth economy, until United State economy experience stagflation. Nothing progress state were prepared help really, they submitted to United State alone contend recession deserving them.The raising of food commodity price enough hit Indonesian import, because corn import, soybean and rice. Indonesia have valuable experience in contend crisis in year 1997 and since last three years Indonesia build energetic of infrastructure, export contribution of PDB only little, until financial crisis of United State very little influence it of Indonesia economy. In a manner macro, Indonesian rigid adequate in contend financial crisis effect from United States proven: stock exchange market bullish (raise 10%), capital investment raise from USS 14,4 billion (2007) become US$16,59 billion (2008). The Agriculture investment raise 56,15% (PMA) and 48,67% (PMDN). PDB Agriculture raise from 3% (2007) become 4,3% (2008), raise credit 22%, financial sector be happen liquid surplus, and growth economic about 6%. However, there were some matters that need obtain attention that is: BI rate be high will pressure real sector, raising of world oil price will pressure APBN and raising unemployment from 7% in 2007 become 8% in 2008